Multi-modal, multi-source reading: A multi-representational reader's perspective. (October 2018) - Ainsworth, Shaaron E.
Abstract: In this commentary, I review the five articles that comprise the Special Issue titled 'Towards a model of multi-source, multi-modal processing". The papers are discussed in terms of how they help us understand the "second generational" issues of reader characteristics, representational choices, task demands and assessment approaches. The commentary concludes by anticipating themes for future work that are common to all the papers' concerns. Highlights: 5 papers are discussed in terms of second generational factors. The commentary writer's task is analysed according to ReSOLV. A synthesis of findings from the papers and the commentator's task is attempted.